Realizing the Gains from Trade : Export Crops, Marketing Costs, and Poverty - Balat, Jorge; Brambilla, Irene; Porto, Guido (World Bank, Washington, DC, 2012)
This paper explores the role of export costs in the process of poverty reduction in rural Africa. The authors claim that the marketing costs that emerge when the commercialization of export crops requires intermediaries can lead to lower participation into export cropping and, thus, to higher poverty. They test the model using data from the Uganda National Household Survey. The findings show that: i) farmers living in villages with fewer outlets for sales of agricultural exports are likely to be poorer than farmers residing in marketendowed villages; ii) market availability leads to increased household participation in export cropping (coffee, tea, cotton, fruits); and iii) households engaged in export cropping are less likely to be poor than subsistence-based households. The authors conclude that the availability of markets for agricultural export crops helps realize the gains from trade. This result uncovers the role of complementary factors that provide market access and reduce marketing costs as key building blocks in the link between the gains from export opportunities and the poor.